Sistema de geração e armazenamento de energia elétrica utilizando transdutor piezelétrico na forma pulsada - Sanches, Fabricio Marqui [UNESP] (2015)
This paper investigated the energy viability of the use of piezoelectric buzzers, rectifier circuit full-wave and DC-DC-converter in a power harvesting systems subjected to mechanical stress caused by the traffic of vehicles and / or walk for pedestrians, demonstrating the possibility of re-use of energy in charging batteries to power autonomous monitoring circuits, display, illumination, etc., in remote locations, eliminating or extending the intervals needed between charges these devices. The piezoelectric generator is analyzed through excitation carried out by a pneumatic cylinder simulator electronically controlled impacts with a frequency of 0.5 Hz and 1 Hz, containing different amounts of PZTs (2, 4, 8) and connection configuration (parallel or serial) . The extracted results are related to the voltage, current, power and energy stored in function of time, still being made relations of these quantities for the number of PZTs, area they occupy, force and pressure applied on them. At the end we can conclude the feasibility of using simple devices in power harvesting systems to generate energy through excitations in pulsed manner and at low frequencies, with higher values in the circuit output in terms of power and current to voltage 5 volts, 108 µW and 21,5 µA (0,53 Kg and 0,83 N/cm2), just like 118,8 µW and 23,6 µA to (2,13 Kg e 3,33 N/cm2), obtained with 8 PZTs, connected in parallel and excited to 1 Hz.